2013
DOI: 10.1177/1087054713493321
|View full text |Cite
|
Sign up to set email alerts
|

Nonmedical Use of Prescription ADHD Stimulant Medications Among Adults in a Substance Abuse Treatment Population

Abstract: Prescription stimulant NMU was low compared with other prescription medications among individuals assessed for substance abuse problems, with little difference among specific products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Studies in non‐Japanese populations have also reported low rates of nonmedical use of prescription stimulants. For instance, in almost 150 000 assessments from the US National Addictions Vigilance Intervention and Prevention Program system, previous 30 day nonmedical use of prescription stimulants (1.3%) was significantly less than that of prescription opioids (19.8%) or sedatives (10.6%) . Among stimulants, nonmedical use of LDX and OROS methylphenidate appeared to be considerably lower than that of short‐acting and long‐acting mixed amphetamine salts, and of short‐acting methylphenidate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in non‐Japanese populations have also reported low rates of nonmedical use of prescription stimulants. For instance, in almost 150 000 assessments from the US National Addictions Vigilance Intervention and Prevention Program system, previous 30 day nonmedical use of prescription stimulants (1.3%) was significantly less than that of prescription opioids (19.8%) or sedatives (10.6%) . Among stimulants, nonmedical use of LDX and OROS methylphenidate appeared to be considerably lower than that of short‐acting and long‐acting mixed amphetamine salts, and of short‐acting methylphenidate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a placebo-controlled, randomized, double-blind, fixed-dose (30,50, or 70 mg/d), phase 2/3 trial in Japanese pediatric patients with ADHD demonstrated marked efficacy for LDX over 4 weeks with no major safety or tolerability concerns. 16 As an extension of the phase 2/3 trial, this open-label study was conducted to evaluate the long-term safety of LDX 30, 50, and 70 mg/d in Japanese children and adolescents with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Most individuals who reported NMU (w50%-90%) obtained the medication from family or friends. 15,20,26,27,30,36,37,40,42,50,55,59,73,78,80,105,106,118 College peers are also an often-cited source, 98,101,104,118 although the peer supplying the medication is not always a friend. 118 Many individuals (4%-35%) reported NMU of their own prescription stimulant.…”
Section: Epidemiology Of Stimulant Nmu and Diversionmentioning
confidence: 99%
“…In a total of 147,816 assessments from the National Addictions Vigilance Intervention and Prevention Program system (2009 through 2012) to assess NMU of prescription ADHD stimulants among adults evaluated for substance abuse treatment, past 30-day NMU for prescription stimulants (1.29%) was significantly lower than that of prescription opioids (19.79%) or sedatives (10.62%), with little difference among specific stimulant products [88]. The realworld abuse potential of LDX is highlighted by NMU data collected from the Researched Abuse, Diversion and Addiction-Related Surveillance System Drug Diversion Program and Poison Center Program in the USA.…”
Section: Treatment Persistence Adherence and Abuse Liabilitymentioning
confidence: 99%